79.8k views
5 votes
Please help on this one?

Please help on this one?-example-1
User Armel
by
6.1k points

1 Answer

4 votes

Answer:

Inverse function: If a function f(x) is mapping x to y, then the inverse function of f(x) maps back y to x

Given that:
y = (2)/(3)x -6

Interchange the variable x and y;


x = (2)/(3)y -6

Add 6 to both sides we get;


x +6= (2)/(3)y -6+6

Simplify:


x+6= (2)/(3)y

Multiply both sides by
(3)/(2) we get;


(3)/(2)(x+6) = y

or


y = (3)/(2)x+ 9

Therefore, the inverse of
y = (2)/(3)x-6 is,


y = (3)/(2)x+ 9

User Justin Chmura
by
5.0k points